How can county-level industrial clusters in China promote urban-rural integration?—A study on the configuration effects based on fsQCA - Gaoyang Liang; Mingqiang Xing; Jianqiang Zhao (PLoS ONE, 2025)
This study explores how county-level industrial clustering in China promotes urban-rural integration by identifying four key pathways: industrial linkage, technology transfer, employment coordination, and service balance. Drawing on a dataset of 343 counties from 2013 to 2023 and applying fuzzy-set Qualitative Comparative Analysis (fsQCA), the research uncovers the configuration effects of these mechanisms. The results reveal three primary models: the industry–technology–employment-driven model, the industry–employment-driven model, and the industrial linkage-dominant model. Further, configuration analyses by cluster type indicate that industrial linkage and service balance are central in agriculture-oriented clusters; employment coordination and technology transfer are critical in industry-oriented clusters; and service balance and employment coordination jointly drive integration in service-oriented clusters. Temporal analysis over the past decade demonstrates a steady strengthening of industrial linkage, a rapid increase in technology transfer, persistently high levels of employment coordination, and gradual improvement in service balance. These findings provide new insights into the multi-pathway dynamics of urban-rural integration and inform differentiated policy approaches based on cluster types.